1995
DOI: 10.1097/00005392-199509000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Blockade in the Treatment of Symptomatic Benign Prostatic Hyperplasia

Abstract: alpha-Blockers were beneficial in the treatment of benign prostatic hyperplasia. Tolerance to treatment appeared to develop in a large proportion of patients after 6 months of therapy. However, for patients who benefit from long-term use of alpha-blockers effective treatment might be maintained for years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 0 publications
2
57
0
Order By: Relevance
“…1 Medical therapy, and particularly alpha-blockade therapy, has been extensively studied in double-blind placebo-controlled studies by urologists on outpatients, and usually in hospital setting. 2 Those ef®cacy studies have consistently demonstrated the ef®cacy and safety of alpha 1 -blocker in the treatment of BPH. 3 In particular alfuzosin has been proven to have a good bene®t/risk ratio.…”
Section: Introductionmentioning
confidence: 99%
“…1 Medical therapy, and particularly alpha-blockade therapy, has been extensively studied in double-blind placebo-controlled studies by urologists on outpatients, and usually in hospital setting. 2 Those ef®cacy studies have consistently demonstrated the ef®cacy and safety of alpha 1 -blocker in the treatment of BPH. 3 In particular alfuzosin has been proven to have a good bene®t/risk ratio.…”
Section: Introductionmentioning
confidence: 99%
“…However, as concern has been expressed over the development of tolerance to alpha-1 adrenoceptor antagtom scores (41-58% vs 12-36%) and total symptom scores (32-44% vs 11-30%). Terazosin was not signifionists [31], further controlled studies of long-term treatment are needed. cantly diÂerent from placebo in its eÂect on residual volume.…”
Section: Alpha Adrenoceptor Antagonists Past and Presentmentioning
confidence: 97%
“…Eri and Tveter [31] have reviewed published results from 29 use in BPH should be very selective for prostatic alpha-1 receptors and produce little or no side-eÂects related to randomized, placebo-controlled trials of alpha-1 selective adrenoceptor antagonists. A total of 3464 patients were systemic or vascular alpha blockade.…”
Section: Alpha Adrenoceptor Antagonists Past and Presentmentioning
confidence: 99%
“…A variety of a 1 blockers are available and their use generally results in a 6 -31% improvement in symptom score within the first 2 -3 weeks. 30,31 Maximum urinary flow rate can also be increased by up to 3.9 ml/s. 30 In terms of sexual function, the effect of the different a 1 blockers on ejaculation is shown in Table 2.…”
Section: Medical Therapymentioning
confidence: 99%
“…30,31 Maximum urinary flow rate can also be increased by up to 3.9 ml/s. 30 In terms of sexual function, the effect of the different a 1 blockers on ejaculation is shown in Table 2. 26,31 -37 The European Tamsulosin Group reported that at 3 y follow-up, 2.9% of patients had ED and 4.3% ejaculation disorders.…”
Section: Medical Therapymentioning
confidence: 99%